Hubungan Perilaku Ibu dengan Pemberian Makanan Pendamping Asi (Mp-Asi) pada Bayi Usia 6-24 Bulan di Puskesmas Perwatan Gumpang Kab. Gayo Lues Prov. Aceh Tahun 2023 - Roliah Roliah; Nur Azizah (Jurnal Siti Rufaidah, 2024)
The provision of appropriate complementary food for breast milk (MP-ASI) is essential to meet the nutritional needs of infants aged 6-24 months. This study analyzes the relationship between maternal behavior, including knowledge, attitudes, and actions, with MP-ASI provision at the Gumpang Health Center, Gayo Lues Regency, Aceh Province. A quantitative method with a descriptive correlational design and cross-sectional approach was used. The sample consisted of 24 mothers with infants aged 6-24 months, selected through purposive sampling. Data were collected via questionnaires and analyzed using the chi-square test. Results showed that most respondents were aged 26-30 years (45.8%), had a high school education (62.5%), and worked as housewives (37.5%). Bivariate analysis indicated a significant relationship between maternal knowledge and MP-ASI provision (p = 0.007), maternal attitudes and MP-ASI provision (p = 0.003), and maternal actions and MP-ASI provision (p = 0.001). Mothers with good knowledge, attitudes, and actions were more likely to provide complementary feeding according to nutritional guidelines. In conclusion, maternal behavior, encompassing knowledge, attitudes, and actions, significantly influences MP-ASI provision. Strengthening maternal education and implementing community-based interventions are necessary to promote optimal infant nutrition.